CYP450 mediated inhibition potential of Swertia chirata: An herb from Indian traditional medicine. (3rd February 2016) - Ahmmed, Sk Milan; Mukherjee, Pulok K; Bahadur, Shiv; Harwansh, Ranjit K; Kar, Amit; Bandyopadhyay, Arun; Al-Dhabi, Naif Abdullah; Duraipandiyan, V.
Abstract: Ethnopharmacological relevance: An Ayurvedic herb, Swertia chirata (SC) have been used in treating various ailments such as hyperglycemia, leishmania, liver infections, inflammation, abdominal pain, bacterial infection, malaria etc. in Indian Systems of Medicine (ISM). Aim of the study: Study was designed to investigate the inhibition potential of the standardized SC extract along with its bioactive molecule ursolic acid on hepatic drug metabolizing isozymes (CYP3A4 and CYP2D6) and further some heavy metals were also analysed of the plant material. Materials and methods: The hydro-alcoholic extract was standardized with standard ursolic acid by reverse phase-high performance liquid chromatography (RP-HPLC) method and the heavy metals content were analyzed through atomic absorption spectroscopy (AAS). The effect of extract on rat liver microsome (RLM) and individual CYP isozymes (CYP3A4 and CYP2D6) was investigated through CYP450-CO complex assay and fluorescence microplate assay respectively. Results: The content of ursolic acid was found to be 2.66% (w/w) in the SC extract and heavy metal contents along with trace elements were within the prescribed limits as per WHO guidelines. The inhibitory potential of SC extract on RLM was found to be 23.64±1.80%. CYP3A4 and CYP2D6 inhibitory effect of SC and ursolic acid (IC50 : 197.49±2.68, 211.45±3.54 and IC50 : 229.25±2.52, 212.66±1.26 µg/mL) was less as compared to that known inhibitors, ketoconazole and quinidine respectively. Conclusions: The current study revealed that S. chirata has less inhibition potential with two major drug metabolizing isozymes CYP3A4 and CYP2D6. SC extract and ursolic acid showed significantly ( P <0.001) less inhibitory potential on RLM. The Ayurvedic herb (SC) has shown less inhibitory activity in a concentration dependent manner against the tested two CYP450 enzymes. The tested heavy metals and trace elements present SC was within limit. Therefore, the traditional use of S. chirata may be safe in respect of both tested isozymes. Graphical abstract: